The Influence of Online Shopping Experiences and Trust on Repurchase Interest in TikTok Shop: (Case Study of Students State Polytechnic Bengkalis) - Siti Maharani; Nageeta Tara Rosa (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This research aims to determine the influence of online shopping experiences and trust on repurchase intention at TikTok Shop. The sample objects in this research are consumers who have made at least 3 purchases on the TikTok Shop application. There were 28 consumers who made purchases 3 times, 5 people made 4 purchases, and 67 people made frequent purchases at the TikTok Shop. This study uses a Quantitative Method using non-probability sampling method with purposive sampling. The sample in this study was 100 respondents, processing data using the SPSS 26 application with multiple linear regression analysis testing which included validity test, reliability test, Ttest, Ftest and the coefficient of determination (R²). The research results show that: Hypothsis 1) online shopping experience has a positive and significant effect on repurchase interest at TikTok Shop, hypothsis 2) trust has a positive and significant effect on repurchase interest at TikTok Shop, hypothesis 3) Trust and Online shopping experience have a positive and significant effect on online repurchase interests the determinant coefficient (R²) is 0.156. This means that the variables of online shopping experience and trust influence repurchase interest at TikTok Shop by 15.6%, while the remainder or 84.4% is influenced by other variables not examined in this research.